2022
DOI: 10.1101/2022.06.21.497058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supercharged Protein Nanosheets for Cell Expansion on Bioemulsions

Abstract: Cell culture at liquid-liquid interfaces, for example at the surface of oil microdroplets, is an attractive strategy to scale up adherent cell manufacturing whilst replacing the use of microplastics. Such process requires the adhesion of cells at interfaces stabilized and reinforced by protein nanosheets displaying high elasticity, but also presenting cell adhesive ligands able to bind integrin receptors. In this report, supercharged albumins are found to form strong elastic protein nanosheets and mediate extr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Recently, the modification of globulins such as albumins with charged residues was found to impact their assembly at liquid–liquid interfaces and resulting nanosheet mechanics . These supercharged protein nanosheets enabled the simple adsorption of cell-adhesive proteins such as fibronectin and collagen, but the strengthening of their mechanical properties still required introduction of PFBC in order to sustain stem cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the modification of globulins such as albumins with charged residues was found to impact their assembly at liquid–liquid interfaces and resulting nanosheet mechanics . These supercharged protein nanosheets enabled the simple adsorption of cell-adhesive proteins such as fibronectin and collagen, but the strengthening of their mechanical properties still required introduction of PFBC in order to sustain stem cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the modification of globulins such as albumins with charged residues was found to impact their assembly at liquid–liquid interfaces and resulting nanosheet mechanics. 11 These supercharged protein nanosheets enabled the simple adsorption of cell-adhesive proteins such as fibronectin and collagen, but the strengthening of their mechanical properties still required introduction of PFBC in order to sustain stem cell proliferation. This study demonstrated that simple protein modification may allow to modulate both nanosheet mechanics and bioactivity, however the identification of proteins and oils that enable the achievement of high interfacial elasticity in the absence of cosurfactant was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the modification of globulins such as albumins with charged residues was found to impact their assembly at liquid-liquid interfaces and resulting nanosheet mechanics 12 . These supercharged protein nanosheets enabled the simple adsorption of cell-adhesive proteins such as fibronectin and collagen, but the strengthening of their mechanical properties still required introduction of PFBC in order to sustain stem cell proliferation.…”
Section: Introductionmentioning
confidence: 99%